LIFE-COURSE AND BIOGRAPHY OF THINGS: MINANGKABAU WOMEN'S HEADGEAR - Denendra, Attari Putri; Marwoto, Irmawati (International Review of Humanities Studies, 2025)
Like men, objects also have a biography or life-course. Both biographies are intertwined, so when someone experiences a new life phase transition in their life-course, it will cause changes in the objects attached to them. This is also supported by the statement that the identity is performative. The headgear as one of the elements used by Minangkabau women also represents the identity of the wearer. This research was conducted in three stages: (1) data collection in the form of old photos and literature of Minangkabau women with headgear in Batipuh, Fort de Kock, and Payakumbuh, (2) data processing by analysis of the data in context space, time, and concepts, then (3) interpretation. The approach used is the Life-Course by Roberta Gilchrist and Biography of Things by Igor Kopytoff, which focuses on age and cultural markers. The research results show that the identity of Minangkabau women is reflected in their headgear, so major life transitions also lead to changes in these headgears, both in terms of form and material. This article also discusses the concept of age in Minangkabau women. It can be a reference for marking the age of Minangkabau women's headgear, examining its relationship to rites passages, like marriage.